“I lit the candle with fire from my heart”: Observing Yom Hashoah (Holocaust Remembrance Day) at a Jewish Home for the Aged - Gould, Jillian (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2012)
At the Yom Hashoa (Holocaust Remembrance Day) ceremony at the Terraces of Baycrest in Toronto, resident survivors sit at a head table facing the room. They are the embodiment of the ceremony: the victims we remember and the survivors before us. As the eyewitnesses of the darkest time in Jewish history, they mourn their family and friends, and the community mourns with them.This paper presents a case study of this unique service, which stands apart because it is situated in a seniors’ residence. Other Holocaust Remembrance Day observances typically take place “outside” in public institutional spaces: synagogues, schools, community centres, museums; but here, residents invite the community “inside”—into the institutional home—and highlights each survivor’s experiences. By giving residents an opportunity to bring to the foreground their individual narratives, Baycrest staff members facilitate the confirmation of each person’s self-worth and sense of identity. In this way, a creative ritual like the Yom Hashoah Ceremony helps residents to face death, mourning, and remembrance in a supportive, familiar environment while contributing to the sense of family, culture, and community shared by the residents and their extended families.